PENGELOLAAN KEUANGAN GEREJA PADA GMIM JEMAAT TIBERIAS KIMA BAJO WILAYAH WORI: Church Financial Management in The GMIM Congregation of Tiberias Kima Bajo Wori Region - Sabijono, Haryanto; Tirayoh, Victorina Zusana; Demmassabu, Langimanapa Sofia; Suwetja, I Gede (Sam Ratulangi University, 2025)
Every existing organization will inevitably come into contact with organizational finances. An organization can run well thanks to financial support, whether in the form of contributions from individual members or from external parties. This also applies to non-profit organizations. Even though they are non-profit, they still deal with organizational funds because there are expenses that must be made for organizational activities or operations. These funds need to be accounted for in order to increase members’ trust in the organization’s administrators or leaders. The church is one example of a non-profit organization. Its purpose is to provide spiritual services to the congregation, which essentially does not demand compensation. However, members respond to this service by giving offerings. These congregational offerings are one of the church’s sources of income, in addition to other sources such as donations from various parties, whether in the form of funds or other assets. All of the church’s assets need to be reported as a form of accountability. Managing church finances is not easy and should not be taken lightly; it requires adequate accounting knowledge. Some financial managers feel they lack understanding of the church’s financial management system. For this reason, the PKM team will provide training on financial management at GMIM TIBERIAS Kima Bajo, Wori District. Those entrusted with managing church finances must be dependable; therefore, understanding how to record church transactions is essential for individuals chosen as treasurers. ABSTRAK Setiap organisasi yang ada pastinya akan bersentuhan dengan keuangan organisasi. Organisasi bisa berjalan dengan baik tidak lepas karena adanya dukungan dana apakah itu sumbangan orang pribadi anggota organisasi maupun yang dari luar organisasi. Begitu juga dengan organisasi nir laba, yaitu organisasi non profit. Sekalipun non profit tapi tidak lepas bersentuhan dengan dana organisasi oleh karena pembiayaan pembiayaan yang harus dikeluarkan dalam rangka kegiatan atau operasional organisasi. Dana tersebut tentunya perlu dipertanggungjawabkan agar dapat meningkatkan rasa kepercayaan anggota terhadap pengurus atau pimpinan organisasi. Gereja merupakan salah satu contoh organisasi non profit. Tujuannya adalah memberikan pelayanan rohani kepada jemaat, yang sebenarnya tidak menuntut imbalan tetapi jemaat dengan kesadaran merespon bagian dari pelayanan itu dengan memberikan persembahan. Persembahan jemaat ini merupakan salah satu sumber pendapatan gereja, di samping sumber yang lain seperti donatur dari berbagai pihak baik berupa dana maupun asset lainnya. Semua asset yang di miliki gereja ini perlu di laporkan sebagi bentuk pertanggungjawaban. Menjadi pengelola keuangan gereja tidaklah mudah dan jangan dianggap enteng, dibutuhkan pengetahuan akuntansi yang cukup. Sebagian pengelola keuangan merasa kurang paham akan sistem pengelolaan keuangan di gereja untuk itu tim PKM akan memberikan penyuluhan mengenai pengelolaan keuangan di GMIM Jemaat TIBERIAS Kima Bajo Wilayah Wori. Menjadi pengelola keuangan di gereja harus dapat diandalkan untuk itu pemahaman akan pencatatan transaksi di gereja harus dimiliki oleh orang orang yang dipilih sebagai pemegang kas.